THE CONTENT AND PHILOSOPHICAL INTERPRETATION OF SUFISISM AND ETHICS ON THE BASIS OF FARIDUDDIN ATTAR AND HIS WORK “TAZKIRAT UL-AVLIYA” - Mirakhmedova Shokhida Nusratilloyevna (Modern American Journals, 2025)
The article discusses the life path of Fariduddin Attar, analysis of his works, the height of his artistic creativity, the unique and famous work “Tazkirat ul-Awliya” written in prose, which deals with the lives of the sheikhs of Sufism, the lives of the saints, their revelations and miracles, and their views on various mystical terms such as Sharia, Tariqat, Enlightenment, Tawakkul, Riza, Sabr, and Shukr.
Keywords: “Tazkirat ul-Awliya”, Mutawakkul and tazkiranavis, sheikhs of Sufism, Sharia, Tariqat, Enlightenment, Tawakkul, Riza, Sabr, Shukr, poetry, parables and sayings, miracle, maqamat, unusual custom, revelation and mathematics, firka.